Supplementary data for: On the Neotropical spider genus Ciniflella Mello-Leitão, 1921 (Araneae: Zoropsidae, Tengellinae) - Ramirez, Martin Javier (2024)
This package contains the supplementary data for the publication: Brescovit AD, Grismado CJ, Almeida-Silva LM, Ramirez MJ. In press. On the Neotropical spider genus Ciniflella Mello-Leitão, 1921 (Araneae: Zoropsidae, Tengellinae). Zootaxa. The package contains the aligned genetic markers in fasta format, and the phylogenetic trees in Newick format. The supplementary figures can be found in Zenodo: https://doi.org/10.5281/zenodo.14182471